Review Model Teknologi Perguruan Tinggi Menurut Sudut Pandang Supply Chains Management - Ilham Albana; Irfan Santiko (Journal of Information Technology Ampera, 2022)
The community's need for higher education is very important. Given the regulations of UU No.234 u 2000 concerning guidelines for the establishment of higher education institutions, it is quite easy for foundations and institutions, several institutions are competing and interesting to establish universities. Higher education is currently an attractive business field. The existence of graduates in the community or the market will always be an attribute of the community's assessment of the original university. If the alumni are well absorbed by the market, the university will get a positive assessment. Every university has an interest in knowing the level of user satisfaction of its graduates as an important part of the evaluation and projections of the institution. Problems arise when graduates are not well absorbed. Many factors could be the cause. In a business, of course, you must look at it from the point of view of market needs, the same thing as higher education institutions. If you don't pay attention to the market aspect, it is certain that graduates are not well absorbed due to lack of quality. In this article, we will discuss the sustainability of business processes in higher education based on user reviews of graduates. The continuity of this business process using a supply chain model approach.